Hubungan Fungsi Keluarga dengan Subjective Well-Being Siswa SMP Negeri di Kota Tasikmalaya Selama COVD-19 - Desy Dewi Suminar; Hedi Wahyudi (UNISBA Press, 2022)
Abstract. Adolescence is a period of transition to adulthood where there are many problems of life, individual conflicts and pressures that come from family, school and external parties. Therefore, children in their teens need attention and direction from their parents. Therefore, the functioning of the family, especially parents, has the potential to affect their subjective well-being . Especially during the COVID-19 pandemic. The purpose of this study was to find out how closely the relationship between family functsion and subjective well-being in State Junior High School students in Tasikmalaya during COVID-19. The research method used is a correlational method with a quantitative approach. The sampling technique used is cluster random sampling. The size of the research sample is 400 students from 21 junior high schools throughout the city of Tasikmalaya. Data collection techniques were carried out using a questionnaire. Furthermore, the data obtained were processed by calculating the Spearman correlation test. The results showed that the relationship between family function and subjective well-being had a strong correlation, with a correlation coefficient of 0.767 with a significance level of 0.000. This means that there is a significant positive relationship between family function and subjective well-being students'during COVID-19. The higher the family function, the higher the subjective well-being of state junior high school students in Tasikmalaya City during COVID-19. Abstrak. Usia remaja merupakan masa transisi menuju usia dewasa dimana pada masa ini bermunculan banyak problematika kehidupan, konflik individual serta tekanan-tekanan yang bersumber dari keluarga, sekolah maupun dari pihak eksternal. Oleh karenanya anak di usia remaja membutuhkan perhatian dan arahan dari orang tuanya. Oleh karena itu, keberfungsian keluarga, terutama orang tua berpotensi memengaruhi subjective well-being mereka. Terutama di masa pandemi COVID-19. Tujuan penelitian ini adalah untuk mengetahui seberapa erat hubungan fungsi keluarga dengan subjective well-being pada siswa SMP Negeri di Tasikmalaya selama COVID-19. Metode penelitian yang digunakan adalah metode korelasional dengan pendekatan kuantitatif. Teknik sampling yang digunakan adalah cluster random sampling. Besarnya anggota sampel penelitian yaitu 400 siswa dari 21 SMP se-Kota Tasikmalaya. Teknik pengumpulan data yang dilakukan dengan menggunakan kuesioner. Selanjutnya, data yang diperoleh diolah dengan perhitungan uji korelasi Spearman. Hasil penelitian menunjukkan hubungan fungsi keluarga dengan subjective well-being memiliki korelasi kuat, yaitu dengan koefisien korelasi sebesar 0.767 dengan taraf signifikansi sebesar 0.000. Artinya terdapat hubungan yang positif signifikan antara fungsi keluarga dan subjective well-being siswa selama COVID-19. Semakin tinggi fungsi keluarga maka semakin meningkat subjective well-being siswa SMP Negeri di Kota Tasikmalaya selama COVID-19.